Polo-like Kinase 1 Expression as a Biomarker in Colorectal Cancer: A Retrospective Two-Center Study - Lana Jajac Brucic; Vesna Bisof; Majana Soce; Marko Skelin; Ivan Krecak; Andjela Nadinic; Branka Vrbicic; Zivana Puljiz; Suzana Hancic; Slavko Gasparov (Biomedicines)
Background/Objectives: Early-onset colorectal cancer (EOCRC) is more frequently characterized by poorly differentiated, aggressive tumors, often diagnosed at advanced stages, and associated with worse prognoses. Despite these differences, current treatment guidelines do not distinguish between EOCRC and late-onset colorectal cancer (LOCRC). Elevated expression of polo-like kinase 1 (PLK-1) has been linked to advanced disease stages and poorer treatment outcomes, including resistance to both chemotherapy and radiotherapy. However, data on PLK-1 expression in EOCRC compared to LOCRC remain limited. Methods: Patients with sporadic CRC, aged >18 years, were included in this study. We categorized the patients into two groups: patients younger than 50 years, and those aged 50 years or older. Immunohistochemical staining was performed to assess PLK-1 expression. The aim of this study was to assess PLK-1 expression considering the age of the patients and its effects on overall survival (OS) and progression-free survival (PFS). Results: A total of 146 patients with metastatic colorectal cancer (mCRC) were included in this retrospective two-center study. Patients with low PLK-1 expression were older than patients with high PLK-1 expression (64 (49–71) years vs. 49 (42–67) years, p = 0.016). Multiple logistic regression confirmed that age is a significant predictor of PLK-1 expression, independent of the covariates (p = 0.036). The Kaplan–Meier analysis revealed no significant association between PLK-1 expression and PFS (p = 0.397) or OS (p = 0.448). Accordingly, Cox proportional hazards regression analysis showed no significant association between PLK-1 expression and OS (HR 1.20, 95% CI 0.73–1.96, p = 0.598) or PFS (HR 0.85, 95% CI 0.51–1.43, p = 0.611) when covariates were taken into account. Finally, no significant differences in PFS (p = 0.423) or OS (p = 0.104) were found between the age groups of interest. Conclusions: PLK-1 expression was not associated with survival or progression in EOCRC and LOCRC patients. Further research on these combinations is necessary, as well as the discovery of new potential targets for targeted therapy and the mechanisms of synergistic effects in tumors with PLK-1 overexpression.